Artificial Intelligence Tools in Educational Support for Students with Special Educational Needs (SEN) in Various Disabilities - Díaz Vera, Janeth Pilar; Pulley Cajamarca, Jamil Josué; Navarrete Llaguno, Paola Salomé (Revista Universidad de Guayaquil, 2025)
This study aims to evaluate the effectiveness and perception of artificial intelligence (AI) tools in educational support for students with Special Educational Needs (SEN) and various disabilities. The research approach is exploratory and applied, using a descriptive and quantitative design. Data were collected through structured surveys administered to a purposive sample of 15 students from the Information Technology program at the University of Guayaquil, who have different types and degrees of disability. These instruments were used according to the specific needs of the students, utilizing tools such as Hetah.net for sign language translation and Microsoft Forms immersive readers for students with visual and physical disabilities. Data analysis was conducted using descriptive statistics, frequency, comparative, and correlational methods. Results indicated that AI tools are perceived as a significant support for learning, improving accessibility and adaptability in the educational process. However, challenges related to the need for further training for both students and teachers were identified. Despite the limitations of the sample, the findings suggest that AI tools have great potential to promote educational inclusion. It is concluded that an integrated approach considering both technological capabilities and user training is essential to maximize the positive impact of these tools.